Modelling parenting styles, moral intelligence, academic self-efficacy and learning motivation among adolescents in grades 7–11. Issue 1 (2nd January 2019) - Alhadabi, Amal; Aldhafri, Said; Alkharusi, Hussain; Al-Harthy, Ibrahim; Alrajhi, Marwa; AlBarashdi, Hafidha
ABSTRACT: The current study investigated the associations between three maternal and paternal parenting styles, moral intelligence, academic self-efficacy and learning motivation in three serial mediation models. Omani adolescents enrolled in 7th to 11th grades ( N = 296) responded to an online survey containing demographic items and scales measuring the variables noted above. Results of Path Analysis indicated that the three models had a good overall fit. In detail, the three paternal styles (authoritative, authoritarian and permissive) had direct associations with moral intelligence and indirect associations with learning motivation. However, only two maternal parenting styles (i.e., authoritative and authoritarian) correlated directly with learning motivation and these two styles did not associate with moral intelligence. All effects were in the hypothesized direction except the effect of authoritative maternal and paternal styles. Moral intelligence had a positive direct correlation with students' academic self-efficacy and learning motivation. Moral intelligence also mediated the negative associations between three types of fathers' parenting styles and students' motivation. Academic self-efficacy had a positive association with students' motivation. These findings provided useful insights about the various association between external factors (e.g., parenting styles), internal factors (i.e., moral intelligence and self-efficacy) and students' motivation among adolescents in middle and high schools.